Pre‐existing interstitial lung disease does not affect prognosis in non‐small cell lung cancer patients with PD‐L1 expression ≥50% on first‐line pembrolizumab - Yamaguchi, Ou (Thorac Cancer, 2020)
BACKGROUND: The safety of pembrolizumab monotherapy in treatment‐naïve non‐small cell lung cancer (NSCLC) patients with high programed death‐ligand 1 (PD‐L1) expression and pre‐existing interstitial lung disease (ILD) has not yet been determined. Here, we aimed to evaluate the prognosis, efficacy and safety associated with pembrolizumab in such settings. METHODS: In this single‐institution retrospective study conducted from May 2017 to October 2019, pembrolizumab was administered to 72 Japanese patients with treatment‐naïve advanced NSCLC with PD‐L1 tumor proportion score (TPS) ≥50%. Patients with ILD were assigned to the ILD group, and those without to the non‐ILD group. Between‐group comparisons were then performed. RESULTS: Of the 72 patients, 61 (84.7%) were male. The median age was 70 years. A total of 64 patients (88.9%) had a smoking history, median PD‐L1 TPS status was 77.5%, and 10 of the 72 patients (13.9%) had ILD on pretreatment computed tomography. The objective response rate (ORR) was 45.8% and disease control rate (DCR) was 75.0%. The ORR was 70.0% and DCR was 90.0% in the ILD group, while the ORR was 41.9% and DCR was 72.6% in the non‐ILD group. The median overall survival was 568 days; the value in the non‐ILD group was 521 days, while in the ILD group was not reached. There was no significant difference between the two groups (log‐lank, P = 0.73). CONCLUSIONS: Pembrolizumab was administered to patients with pre‐existing ILD with no difference in prognosis compared to patients without ILD. In patients with ILD, physicians should consider the expected long‐term prognosis and risk of adverse events.